Study of the energy management information system (EMIS) implementation in Malaysia - Rupadi N.; Ramli S.N.; Mardappan K.; Mohamed H. (American Institute of Physics Inc., 2024)
The Efficient Management of Electrical Energy Regulation 2008 (EMEER 200) requires periodical reporting from affected installations every six months. To analyse the reports submitted to Energy Commission (EC) and present it in a meaningful way, the Energy Management Information System (EMIS) was developed and launched in 2018 to be usedby all parties involved in the compliance of EMEER 2008. Using the system, EC is able to manage the installation and Registered Electrical Energy Manager database more efficiently and track the performance of each installation thoroughlyin efforts of compliance to the regulation. This paper focuses on the need of EMIS replacing the old hard copy report submission method, as well as how EMIS functions and presents the data available in clear statistical manner for the benefitof all the users of the system. Examples of how the user data and analysis results are also presented in this paper. 2023 AIP Publishing LLC.